Markets and Traders in Bukittinggi Town in Early 20th Century Photography (1900-1939) - Ikhsan, Musfiratul Aini; Asnan, Gusti; Nopriyasman, Nopriyasman (UNIVERSITAS MUHAMMADIYAH METRO, 2025)
This study aims to represent photographs of markets and traders in Bukittinggi during the colonial period. This study is included in the study of photographic historiography. This type of research is a literature study using historical methods consisting of four stages. The first stage of this study is heuristics or source collection. The collection of sources is in the form of photographs of markets and traders in Bukittinggi City, books, journal articles, newspapers and others. The second stage is source criticism to validate data from the collected sources. The third stage is interpretation which interprets photographs using the theory of representation as a tool to re-present photographs of markets and traders as objects by giving meaning to them. The fourth stage is historiography or writing history. The results of this study show photographs of the Pasar Atas and the Pasar Bawah with their physical conditions in the form of facilities and infrastructure. Photos of traders women with the types of goods they trade are agricultural product and male traders with their services.